Der Erwerb der Schreibkompetenz im Deutsch als Fremdsprache – zwischen Konzepten und Modellen - KOSEVSKI PULJIĆ, BRIGITA (Wydawnictwo Naukowe UAM, 2009)
The common issue of writing concepts is modelling of the processes which can increase the ability of acquiring the writing competence. It is necessary to consider different aspects included in the process of acquiring the writing ability: cognitive, communicative, language productive, language receptive, language reflexive, rational and emotional aspects.
The acquiring of writing competence in German as a foreign language – concepts and models
Keywords: Writing competence writing concepts, writing as a process, writing as learning, creative writing, rational and emotional aspects, modelling; Writing concepts; Writing as a process; Writing as learning; Creative writing; Rational and emotional aspects; Modelling